DESIGN VALIDATION OF REVISED BLOOM TAXONOMY ORIENTED LEARNING DEVICES ON ELASTICITY MATERIALS FOR PHYSICS IN HIGH SCHOOL - Halima Aini; Amali Putra; Monika Nur (PILLAR OF PHYSICS EDUCATION, 2021)
The development of science and technology in the 21st century is marked by the use of brain work, which is more important than muscle work which has been replaced by intelligent robots. Therefore, efforts to increase the quantity and quality of knowledge through thinking and reasoning exercises are very important to be applied in education. However, after 8 years of implementing K-13, the conditions in the field documents for teacher learning tools show that they still do not meet these expectations. This study aims to develop high school physics learning tools oriented to the revised Bloom's taxonomy on elasticity material. This research is included in Research and Development (RnD) by applying ADDIE. The stages carried out only reached the development stage (validation) which involved 3 lecturers from the Department of Physics FMIPA UNP and 3 physics teachers in Kuantan Singingi Regency as a team of experts and a team of practitioners. The results showed that the feasibility of the resulting product design for lesson plans obtained an average validation value of 82.37% (very valid), and an average validation value of 80.39% (valid). For teaching materials, the average result of lecturer validation is 86.49% (very valid), and the average value of teacher validation is 87.87% (very valid). For the evaluation instrument, the average value of lecturer validation is 79.48% (valid), and the average value of teacher validation is 76.24 % (valid). In general, this study concludes that the resulting learning device designs are in the category between valid and very valid.